Boats in the Harbor at Monterey. - Albert Walton DeRome (n.d.p. Al Aagard), cousin of Carol Henning:::Creator::::::::::::
A photo of lighters, which were barges towed by lampara fishing boats to hold catch, most likely in Harbor Wharf number 2 AKA Fisherman's Wharf in Monterey.